On the Perception and Use of Information from Social Media in Investigative Police Work: Findings from a Scandinavian Study. (25th May 2020) - Rønn, Kira Vrist; Rasmussen, Bjørn K; Skou Roer, Thomas; Meng, Christian
Abstract: The purpose of this article is to report from a qualitative Scandinavian study with the aim of shedding some light on how investigators in the Scandinavian police services perceive the use of information from social media in investigative police work. Based on 12 group interviews and 49 informants from Danish, Norwegian, and Swedish police services, we present three overarching themes mirroring the general perception amongst the interviewed investigators that: (1) information from social media is valuable in almost all types of crime investigation; (2) the use of social media information is fraught with technical pitfalls resulting in a general fear of making mistakes; (3) the legal frameworks governing digital investigative action are vague, leading to a feeling amongst the investigators of working in a grey zone. Overall, the informants express the view that this seemingly unregulated part of investigative work requires a major overhaul.